2007
DOI: 10.1038/ncb1660
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-dependent anchoring of a stem-cell niche

Abstract: SummaryInteractions between stem cells and their surrounding microenvironment, or niche, are critical for the establishment and maintenance of stem cell properties 1 . The adult Drosophila testis contains a discrete morphological stem cell niche, the 'hub', that provides an excellent model for the study of niche development 2-4 . The small cluster of non-dividing, somatic hub cells at the anterior tip of the fly testis is contacted by the germline stem cells (GSCs) 5 that retain their stem cell character throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
226
3
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(245 citation statements)
references
References 29 publications
14
226
3
2
Order By: Relevance
“…In this, they may be analogous to the hub cells present in the Drosophila gonadal niches where cell-cell interaction between hub and stem cell are required to maintain the latter in an undifferentiated state, in the SEZ providing signals that cannot be transmitted via the basal process [18,19]. However, our observations do not argue against conclusions from recent experimental work that the vasculature plays a critical role in supporting stem/ precursor cell proliferation [4][5][6].…”
Section: Kazanis and Ffrench-constantcontrasting
confidence: 56%
“…In this, they may be analogous to the hub cells present in the Drosophila gonadal niches where cell-cell interaction between hub and stem cell are required to maintain the latter in an undifferentiated state, in the SEZ providing signals that cannot be transmitted via the basal process [18,19]. However, our observations do not argue against conclusions from recent experimental work that the vasculature plays a critical role in supporting stem/ precursor cell proliferation [4][5][6].…”
Section: Kazanis and Ffrench-constantcontrasting
confidence: 56%
“…46 Fourth, lack of ␤1 integrin in Drosophila melanogaster gonad stem cells damages the stem cell niche. 47 Our study also showed decreased expression of several other stem cell markers (cytokeratin 15 and ␣6 integrin) in KS skin. Taken together, the data raise the possibility that defective or absent FFH1 may be linked to an epidermal stem cell defect.…”
Section: Discussionmentioning
confidence: 63%
“…In monolayer, provision of a free surface may act as an injury response to initiate cell division, whereas 3D culture might provide equivalent signals on all cell surfaces. β 1 -Integrin signals are important for maintaining the architecture of the niche and also for establishing the orientation of cell division [28,42,43]. Asymmetric divisions are important to control maintenance or exit from the niche, and it is likely that monolayer culture provides an exit signal while 3D provides a maintenance signal.…”
Section: Discussionmentioning
confidence: 99%